Metabolic reprogramming in cancer cells, consequences on pH and tumour progression: Integrated therapeutic perspectives with dietary lipids as adjuvant to anticancer treatment. (April 2017) - Dumas, Jean-François; Brisson, Lucie; Chevalier, Stéphan; Mahéo, Karine; Fromont, Gaëlle; Moussata, Driffa; Besson, Pierre; Roger, Sébastien
Abstract: While tumours arise from acquired mutations in oncogenes or tumour-suppressor genes, it is clearly established that cancers are metabolic diseases characterized by metabolic alterations in tumour cells, and also non-tumour cells of the host organism resulting in tumour cachexia and patient weakness. In this review, we aimed at delineating details by which metabolic alterations in cancer cells, characterized by mitochondrial bioenergetics deregulations and the preference for aerobic glycolysis, are critical parameters controlling the aggressive progression of tumours. In particular, metabolic alteration in cancer cells are coupled to the modulation of intracellular and extracellular pH, epithelial-to-mesenchymal transition and associated increased invasiveness, autophagy, and the development of anticancer treatment resistance. Finally, based on mechanistic, pre-clinical and clinical studies, we proposed the adjuvant supplementation of dietary n-3 polyunsaturated fatty acids for a complementary holistic treatment of the cancer disease.